Preparation and electrochemical studies of electrospun phosphorus doped porous carbon nanofibers - Liu, Chao; Shi, Gaofeng; Wang, Guoying; Mishra, Puranjan; Jia, Shiming; Jiang, Xia; Zhang, Peng; Dong, Yucan; Wang, Zhao (Royal Society of Chemistry, 2019)
An ultra-facile fabrication process for the preparation of phosphorus doped porous carbon nanofibers (P-PCNFs) through the electrospinning and heat treatment method has been studied. The materials were characterized by X-ray diffraction, scanning electron microscopy, and X-ray photoelectron spectroscopy. Studies showed that fabricated P-PCNFs have unique porous fibers structures, large specific surface area (462.83 cm2 g−1), and abundant microporous and mesoporous structures. X-ray photoelectron spectroscopy analyses revealed that the contents of phosphorus and electrochemical properties in a series of P-PCNF samples can be tuned by controlling the polyphosphoric acid concentration. The electrochemical properties of the materials were evaluated using cyclic voltammetry, galvanostatic charge–discharge, and electrochemical impedance spectroscopy. Studies showed that the specific capacitance of the fabricated P-PCNFs using the ultra-facile process reached up to 228.7 F g−1 at 0.5 A g−1 in 1 M H2SO4. Over 84.37% of the initial capacitance remains as the current density increases from 0.5 to 10 A g−1. Meanwhile, at a current density of 2 A g−1, no capacitance loss was observed in 5000 charge/discharge cycles. The highest voltage windows of sample P-PCNFs-1.0 in 1 M H2SO4 aqueous electrolyte can reach 1.4 V. These properties suggest that the fabricated P-PCNFs exhibit excellent electrochemical properties. Conclusively, the surface of carbon nanofibers can be modified by heteroatom doping or surface activation which can improve the electrochemical performance of the materials.